EFFICACY ANALYSIS OF ABDOMINAL BIRTH IN KRASNODAR KRAI - I. I. KUTSENKO; I. O. BOROVIKOV; M. V. GALUSTYAN; V. G. ABUSHKEVICH (Кубанский научный медицинский вестник, 2017)
Aim. To perform the efficacy analysis of abdominal birth in maternity hospitals in Krasnodar Krai based on the ratio of efficiency of caesarean section (RECS). Materials and methods. A multicenter retrospective study was conducted, which included 47 maternity hospitals of Krasnodar Krai in 2016 (number of births, the percentage of surgical activity, perinatal mortality). Calculation of the ratio of efficiency of cesarean section in each of these health institutions was made. Results. Comparative analysis of the ratio of efficiency of caesarean section has revealed the high RECS in Krasnodar Krai (an average of 8,5±0,9, p>0.05). “Bad” ratio (RECS below 1.0) met 9 health establishments of Krasnodar Krai (19,1%), “satisfactory” (RECS 1.0-1.5) - 12 hospitals and “excellent” (RECS 2,0 and above) - 26 maternity hospitals. Conclusion. The effectiveness of abdominal delivery in Krasnodar Krai is high. A detailed individualized analysis of the indications for the operative births is necessary. The most effective is the creation of diagnostic coefficients of risk factors for abdominal delivery, optimization of the routing of pregnant women with complications of gestation, extragenital pathology, premature births in hospitals of the III level, and the transition of all obstetrical institutions of the region to a unified classification of M.S. Robson, which will allow not only to give a more complete analysis of the indications for cesarean section, but also to identify ways to reduce this indicator at each obstetric hospital.